Slips of the Tongue and Pauses in Rigen Rakelna’s Utterances in the Comedy Program Target Operasi: A Psycholinguistic Study - Parto; Putri Sabrina Aulia; Juariyah (LingLit Journal Scientific Journal for Linguistics and Literature, 2026)
Rigen Rakelna has a fast and spontaneous speaking style, which can increase the chances of slips of the tongue and pauses occurring in the produced utterances. The purpose of this study is to determine Rigen Rakelna's utterances that experience slips of the tongue, pauses, and also the causative factors of Rigen Rakelna's slips of the tongue and pauses in the comedy program Target Operasi. This study uses a descriptive qualitative research type because it describes the types of slips of the tongue, pauses, and their causative factors that occur in Rigen Rakelna's utterances in the comedy program Target Operasi. Data analysis techniques in this study consist of data reduction, data presentation, and conclusion drawing as well as verification. Based on the results the types of slips of the tongue that occur in Rigen Rakelna in the Target Operasi comedy program are semantic types, word blends, anticipation, and perseveration types. Meanwhile, the pauses are two, namely pauses pauses and filled pauses. In the type of filled pauses, various forms or sounds were found, including the sound eee, the phrase inian, and ini yaa. This study also found that the main factors causing slips of the tongue and pauses in Rigen Rakelna's utterances in the Target Operasi comedy program are unpreparedness and forgetfulness.